2021
DOI: 10.1093/tas/txab095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drying and providing supplemental oxygen to piglets at birth on rectal temperature over the first 24 h after birth

Abstract: Neonatal piglets can experience both a decrease in body temperature and hypoxia, increasing risks for pre-weaning mortality. This research evaluated the effects of drying and providing supplemental oxygen to newborn piglets on rectal temperature (RT) over the first 24 h after birth. The study used a CRD with 3 Intervention Treatments (IT; applied at birth): Control (no intervention), Drying (dried using a desiccant), Oxygen [dried using a desiccant and placed in a chamber (at 40% oxygen concentration) for 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In this context, the oxygen supply of neonatal piglets is one of the promising strategies reported in the literature; e.g., the recent study of Soraci et al 36 have demonstrated that oxygen supply improved physiological and productive parameters of piglets born with signs of asphyxia or very low birth weight. However the study of Vande Pol et al 37 have revealed that drying of piglets and oxygen supply provided no additional benefit over drying alone, which is contradicting to what reported of Soraci et al 36 and calling for more research.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this context, the oxygen supply of neonatal piglets is one of the promising strategies reported in the literature; e.g., the recent study of Soraci et al 36 have demonstrated that oxygen supply improved physiological and productive parameters of piglets born with signs of asphyxia or very low birth weight. However the study of Vande Pol et al 37 have revealed that drying of piglets and oxygen supply provided no additional benefit over drying alone, which is contradicting to what reported of Soraci et al 36 and calling for more research.…”
Section: Discussionmentioning
confidence: 85%
“…Their findings suggested that piglets’ colostrum intake was affected by breed, while colostrum yield did not differ significantly between breeds. Thus, Declerck et al 37 has claimed that the association between breed and colostrum intake besides litter size was affected by other breed factors, such as udder morphology or teat access. However, in the present study neither assessment of the sow-associated factors was performed nor interrelationship between sow- and/or piglet-associated factors was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional temperature measurement method, rectal temperature is still widely used in actual animal production [ 16 , 95 ]. However, the process of rectal temperature measurement would cause discomfort and quickly produce contact stress [ 96 ].…”
Section: Applications Of Irt Imaging Technology In Animal Productionmentioning
confidence: 99%
“…Neonatal piglets are susceptible to hypothermia during the first several hours after birth because of a combination of a sparse hair coat, a lack of body fat, and limited body surface insulation (Vande Pol et al, 2021;Xiong et al, 2018). They are born wet, and energy is lost from their body surface when residual amniotic fluid is evaporated, causing the evaporative cooling of piglet skin (Curtis, 1970).…”
mentioning
confidence: 99%
“…Pattison et al (1990) quantified piglet rectal temperatures from 10 to 90 minutes after birth with 10 minute intervals, and from 2 to 36 hours with 1 hour intervals. Nowland et al (2020) andVande Pol et al (2021) summarized piglet rectal temperatures measured at 10, 1440, and 4320 minutes after birth and at 0, 20, 30, 45, 60, 120, and 1440 minutes after birth, respectively, although their studies were conducted with additional treatments, such as caffeine supplementation, toweling or desiccant drying, and supplemental oxygen. Contactless infrared thermography combined with machine learning modeling may provide a better estimation of body temperature for supplemental heating device controls and thus decrease the probability of mortality within the first day of birth (Marchant et al, 2000).…”
mentioning
confidence: 99%